Ablation mechanism and properties of silica fiber-reinforced composite upon oxyacetylene torch exposure. (November 2016) - Shi, Shengbo; Gong, Chunlin; Liang, Jun; Fang, Guodong; Wen, Lihua; Gu, Liangxian
The mechanism of mass loss and endothermic properties of silica fiber-reinforced phenolic composites during ablation were investigated in this paper. A theoretical prediction model combining the surface ablation theory and heat transfer theory of heat shield was developed to study the surface ablation behavior. In the formulation of the mathematical model, the effect of the moving boundary on the thermal response was considered, which results from the surface recession of the material in the thickness direction during ablation. The surface ablation recession rate and wall temperature of silica fiber-reinforced phenolic composite specimen were measured using an oxyacetylene torch experimental platform. Then, the efficiency of the model was verified by comparing calculation and experimental results. According to the principles of energy conservation on the ablated surface of the material, the proportion formulas of the heat absorption induced by individual endothermic mechanisms and the total heat absorption were derived. Similarly, the proportions of the mass loss caused by individual mass loss mechanisms were also given. Finally, variations of the ablation properties of the silica fiber-reinforced phenolic composites versus thermal exposure time were calculated and analyzed.